Campylobacter : a practical approach to the organism and its control in foods - Bell, C. , 1946-; Kyriakides, Alec (Chichester, West Sussex, U.K. ; Ames, Iowa : Wiley-Blackwell, 2009)
Campylobacter is the most common cause of bacterial food poisoning with over 400 million cases worldwide reported each year.
1. Background -- 2. Outbreaks : causes and lessons to be learnt -- 3. Factors affecting growth and survival of Campylobacter -- 4. Industry focus : control of Campylobacter -- 5. Industry action and reaction -- 6. Test methods -- 7. The future
Includes bibliographical references and index
Keywords: Campylobacter; Campylobacter infections; Food -- Microbiology